2014
DOI: 10.15740/has/tajas/9.2/119-123
|View full text |Cite
|
Sign up to set email alerts
|

Studies on chemical changes in Shrikhand prepared from safflower milk

Abstract: Shrikhand was prepared from buffalo milk blended with 50 per cent safflower milk and studied for chemical changes during storage. On an average the Shrikhand contained 8.56 per cent fat, 5.81 per cent protein, 43.74 per cent lactose, 0.72 per cent ash and 58.83 per cent total solids and 41.17 per cent moisture. The pH of Shrikhand stored at 10 0 C was 4.2, 4.1, 3.9 and 3.7 while the acidity was 1.42, 1.58, 1.71 and 1.85 per cent, on day 14, 28, 42 and 56, respectively. The pH of Shrikhand stored at 30 0 C was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…When compared with control, optimised Shrikhand samples showed a significantly (p< 0.01) lower tyrosine content throughout the storage. The results obtained were in accordance with the results of Kuttabadkar et al (2014).…”
Section: Changes In Chemical Quality Of Lutein Incorporated Calcium A...supporting
confidence: 91%
See 1 more Smart Citation
“…When compared with control, optimised Shrikhand samples showed a significantly (p< 0.01) lower tyrosine content throughout the storage. The results obtained were in accordance with the results of Kuttabadkar et al (2014).…”
Section: Changes In Chemical Quality Of Lutein Incorporated Calcium A...supporting
confidence: 91%
“…When compared with control, optimised Shrikhand samples showed a significantly (p< 0.05) lower FFA values throughout the storage. Kuttabadkar et al (2014) observed that increase in free fatty acid content of Shrikhand prepared from safflower milk was faster when stored at higher temperatures.…”
Section: Changes In Chemical Quality Of Lutein Incorporated Calcium A...mentioning
confidence: 95%